The Heavens Declare: A Journey through the Seven Skies of Scripture and Science - Belay Sitotaw Goshu; Muhammad Ridwan (Matondang Journal, 2026)
The notion of the seven heavens (ሰባቱ ሰማያት; al-samāwāt al-sabʿ), articulated in Ethiopian Orthodox, biblical, and Islamic traditions, has often been dismissed as prescientific cosmology incompatible with contemporary astrophysics. Such critiques, however, overlook the theological depth and symbolic intentionality embedded within these cosmological visions. Rather than functioning as empirical blueprints of the universe, the seven heavens operate as structured metaphysical frameworks that articulate transcendence, divine sovereignty, and graded ontological reality. This study contends that the seven heavens should be interpreted as a theological architecture rather than a failed scientific hypothesis. Through comparative textual analysis of the Ethiopian Book of Enoch, Pauline references to the “third heaven,” and Qur’anic descriptions of layered heavens, the research demonstrates that each tradition employs vertical cosmology to express divine proximity, moral hierarchy, and spiritual ascent. A hermeneutical engagement with atmospheric science, astronomy, and cosmology further reveals structural correspondences between ancient symbolic stratification and the layered organization of the observable universe, including atmospheric divisions, galactic hierarchies, and large-scale cosmic structures. To conceptualize this relationship, the study introduces the term cognitive resonance, distinguishing meaningful structural parallelism from simplistic concordism. The findings indicate that ancient cosmologies and modern scientific models share analogous patterns of order and scale without implying literal equivalence. Consequently, the heavens function as theological symbols within scripture and as physical realities within science, representing complementary epistemic domains.